The revisioners : a novel - Sexton, Margaret Wilkerson (Counterpoint, 2019)
In 1925, Josephine is the proud owner of a thriving farm. As a child, she channeled otherworldly power to free herself from slavery. Now, her new neighbor, a white woman named Charlotte, seeks her company, and an uneasy friendship grows between them. But Charlotte has also sought solace in the Ku Klux Klan, a relationship that jeopardizes Josephine's family. Nearly one hundred years later, Josephine's descendant, Ava, is a single mother who has just lost her job. She moves in with her white grandmother Martha, a wealthy but lonely woman who pays her grandchild to be her companion. But Martha's behavior soon becomes erratic, then even threatening, and Ava must escape before her story and Josephine's converge.